2022
DOI: 10.1021/acsomega.2c00028
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Induces Nrf2 Mediated Adaptive Homeostasis: Implication for Mercuric Chloride-Induced Nephrotoxicity

Abstract: Background: the primary function of the kidney is to eliminate metabolic waste products and xenobiotics from the circulation. During this process, the kidney may become vulnerable to toxicity. Objective: it was aimed to investigate the impact of thymoquinone (TQ) in mercuric chloride (HgCl 2 )-induced nephrotoxicity through estimation of various proteins involved in natural defense mechanisms. Material and methods: HgCl 2 (0.4 mg/kg) was administered to all groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This protection may be attributed to the restoration of antioxidant enzymes such as CAT, GR, GSH, and GST and a decrease in oxidative stress markers (OH) that reduced the accumulation of HgCl 2 in the kidneys and protected them from damage ( Table 4 ). Besides ECP, various medicinal plants such as Adansonia digitata, ( 67 ) curcumin, 68 flaxseeds, 69 Nigella sativa, 70 Polygonum minus, 71 pomegranate seed, 72 Rheum turkestanicum , 45 and Tribulus terrestris ( 73 ) protect the kidneys from HgCl 2 -induced renal damage by increasing antioxidant enzymes and decreasing oxidative stress markers. 73 75 However, in this study, 600 mg/kg b.w.…”
Section: Resultsmentioning
confidence: 99%
“…This protection may be attributed to the restoration of antioxidant enzymes such as CAT, GR, GSH, and GST and a decrease in oxidative stress markers (OH) that reduced the accumulation of HgCl 2 in the kidneys and protected them from damage ( Table 4 ). Besides ECP, various medicinal plants such as Adansonia digitata, ( 67 ) curcumin, 68 flaxseeds, 69 Nigella sativa, 70 Polygonum minus, 71 pomegranate seed, 72 Rheum turkestanicum , 45 and Tribulus terrestris ( 73 ) protect the kidneys from HgCl 2 -induced renal damage by increasing antioxidant enzymes and decreasing oxidative stress markers. 73 75 However, in this study, 600 mg/kg b.w.…”
Section: Resultsmentioning
confidence: 99%
“…It is often grown in Asian and Mediterranean countries and is widely used in traditional medicine. The seeds of this plant and their essential oils are the bioactive component of thymoquinone (TQ) (2-isopropyl-5-methylbenzo-1, 4-quinone, MW = 164.2) . A wide variety of pharmacological activities of TQ such as anti-inflammatory, immunostimulant, antioxidant, antimicrobial, antidiabetic, hepatoprotective, and cardioprotective have been reported. However, chemotherapeutic and chemopreventive effects of TQ in cancer have also been reported . In different preclinical studies, it has been shown that TQ plays a beneficial role in the control of inflammatory diseases due to its strong antioxidant activity .…”
Section: Introductionmentioning
confidence: 99%